Do the organization types of audit firms matter to earnings conservatism? Evidence from China - Tzu-Ching Weng (Investment Management & Financial Innovations, 2017)
This study explores whether legal liability of audit firms is associated with client’s earnings conservatism. In China, audit firms are allowed to choose between legal forms of general partnership (GP) and limited liability corporation (LLC). Because partner auditor is personally liable for all partners’ service in general partnership form, that will provide an incentive for audit partners to monitor each other’s audit quality. Conversely, personal assets of individual partner, under LLC, are no longer available to pay a partnership’s liability, thus reducing the incentives for intrafirm monitoring by partners within an audit firm. Using several different methods for identifying earnings conservatism, this study finds that LLC audit firms are associated with reduced conservatism.